2013
DOI: 10.3389/fnhum.2013.00746
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation, attention to emotion, and the ventral attentional network

Abstract: Accounts of the effect of emotional information on behavioral response and current models of emotion regulation are based on two opposed but interacting processes: automatic bottom-up processes (triggered by emotionally arousing stimuli) and top-down control processes (mapped to prefrontal cortical areas). Data on the existence of a third attentional network operating without recourse to limited-capacity processes but influencing response raise the issue of how it is integrated in emotion regulation. We summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 295 publications
(423 reference statements)
10
82
1
Order By: Relevance
“…Reingold and Stampe (2004) have previously noted that between participant-variability in saccadic inhibition is very low; they showed that it did not matter whether one used individual or pooled data for analysing the dips in the latency distribution. As would be expected, the effect sizes in previous studies using saccadic inhibition have been very high (N = 64 reported effects, mean r = 0.82, SD = 0.11) (Buonocore & McIntosh, 2012, 2013Reingold & Stampe, 2000.…”
Section: Participantssupporting
confidence: 65%
See 1 more Smart Citation
“…Reingold and Stampe (2004) have previously noted that between participant-variability in saccadic inhibition is very low; they showed that it did not matter whether one used individual or pooled data for analysing the dips in the latency distribution. As would be expected, the effect sizes in previous studies using saccadic inhibition have been very high (N = 64 reported effects, mean r = 0.82, SD = 0.11) (Buonocore & McIntosh, 2012, 2013Reingold & Stampe, 2000.…”
Section: Participantssupporting
confidence: 65%
“…This dichotomy between 'automatic' and 'voluntary' processes remains embedded in many contemporary articles across a variety of disciplines: for example in spatial attention (Barbot, Landy, & Carrasco, 2012;Chica, Bartolomeo, & Lupiáñez, 2013;Ibos, Duhamel, & Ben Hamed, 2013;Macaluso & Doricchi, 2013;McAuliffe, Johnson, Weaver, Deller-Quinn, & Hansen, 2013;Mysore & Knudsen, 2013;D. T. Smith, Schenk, & Rorden, 2012); temporal attention (Lawrence & Klein, 2013); cognition (Lifshitz, Bonn, Fischer, Kashem, & Raz, 2013); motor cueing (Martín-Arévalo, Kingstone, & Lupiáñez, 2013); reading (Feng, 2012); perception (Pfister, Heinemann, Kiesel, Thomaschke, & Janczyk, 2012;Spence & Deroy, 2013); social cognition/perception (Laidlaw, Risko, & Kingstone, 2012) or emotion regulation (R. Viviani, 2013). Similarly, 'voluntary' and 'automatic' actions are clearly distinguished in clinical literature, for conditions ranging from deafness (Bottari, Valsecchi, & Pavani, 2012), to…”
Section: Understanding Automaticity and Volitionmentioning
confidence: 99%
“…The second interesting fact is that in children with RDSP we analysed, we found a posterior-anterior gradient in the localization of the altered PVWM areas, in two cases with involvement of the deep WM of temporal and parietal areas, and this seems to be in accordance with the estimated dysfunction of the associative posterior and limbic areas, with an inevitable impact on the child's emotional sphere too [20].…”
Section: Discussionsupporting
confidence: 49%
“…The potential for emotional stimuli to attract or capture attention has been demonstrated in emotional Stroop (Phaf & Khan, 2007), dot-probe (Mogg, Bradley, De Bono, & Painter, 1997), visual search (Öhman, Flykt, & Esteves, 2001), and spatial cueing tasks (Fox, Russo, & Dutton, 2002); and their competitive advantage has been attributed to emotion-specific gain control mechanisms that are at least partly independent of classical bottom-up and top-down attentional mechanisms (Pourtois et al, 2013;Viviani, 2013). Indeed, some authors have argued that attention to emotional stimuli might be "impenetrable to cognitive control" (Öhman & Mineka, 2001, p. 483; see also Aue, Geux, Chauvigné & OkonSinger 2013;Aue, Chauvigné, Bristle, Okon-Singer, & Geux, 2016), meaning that top-down processes might fail to regulate responses to emotional distractors.…”
Section: The Current Studymentioning
confidence: 99%